Pemikiran Pendidikan Humanistik dalam Islam - Rahman, Musthofa (STAI ALHIKMAH Jakarta, 2017)
Since its birth, Islam has brought a humanitarian mission as it is manifested in the apostolate of Muhammad with the main vision of mercy and kindness to humankind. Islamic education is built on the humanitarian mission with a goal to humanize humans (humanization). In other words, Islamic education is very close to human values. The thought about education that humanizes humans brings to the concept of humanistic education. The concept of humanistic education is strongly influenced by three philosophical thoughts namely pragmatism, progressivism, and existentialism. Each of them contributes a lot to the thoughts of humanistic education. Humanistic is interpreted more asone approach of education that uses humanism approach. This paper explores the process of humanizing humans (humanization) in the concept of humanistic education as an issue and the main goal since the birth of Islam. The process of humanizing people in Islamic education is manifested in the process of humanization, liberation, and transcendence which have strong roots in the teachings of Islam. Keywords: Islam, education, humanistic, and humanization. Sejak kemunculannya, Islam membawa misi kemanusiaan sebagaimana termanifestasi dalam kerasulan Muhammad dengan visi utama memberikan rahmat dan kebaikan kepada seluruh umat manusia. Pendidikan Islam dibangun di atas misi kemanusiaan tersebut dengan tujuan memanusiakan manusia (humanisasi). Dengan kata lain, pendidikan Islam sangat dekat dengan nilainilai kemanusiaan. Pemikiran mengenai pendidikan yang memanusiakan manusia itulah yang melahirkan konsep pendidikan humanistik. Konsep pendidikan humanistik sangat dipengaruhi oleh tiga pemikiran filsafat yaitu pragmatisme, progresivisme, dan eksistensialisme. Masing-masing dari ketiga pemikiran tersebut memberi kontribusi besar bagi bangunan pemikiran pendidikan humanistik. Humanistik lebih dimaknai sebagai salah satu pendekatan pendidikan yang menggunakan kacamata humanisme. Tulisan ini mengetengahkan proses memanusiakan manusia (humanisasi) dalamkonseppendidikanhumanistiksebagaipersoalan yang sudah sejak kemunculan Islam menjadi tujuan utama.Proses memanusiakan manusia dalam pendidikan Islam termanifestasikan dalam proses humanisasi, liberasi, dan transendensi yang memiliki akar kuat dalam ajaran-ajaran Islam. Kata kunci: Islam, pendidikan, humanistik, humanisasi